Proceedings of the 5th Augmented Human International Conference 2014
DOI: 10.1145/2582051.2582089
|View full text |Cite
|
Sign up to set email alerts
|

Using smart phone mobility traces for the diagnosis of depressive and manic episodes in bipolar patients

Abstract: In this paper we demonstrate how smart phone sensors, specifically inertial sensors and GPS traces, can be used as an objective "measurement device" for aiding psychiatric diagnosis. In a trial with 12 bipolar disorder patients conducted over a total (summed over all patients) of over 1000 days (on average 12 weeks per patient) we have achieved state change detection with a precision/recall of 96%/94% and state recognition accuracy of 80%. The paper describes the data collection, which was conducted as a medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 17 publications
(25 reference statements)
1
126
1
Order By: Relevance
“…Among the pioneer projects, the MONARCA project used a variety of phone sensors such as GPS and accelerometer to detect the mental states as well as changes in mental states of bipolar patients [9]. In their study that involved 12 patients over a period of 12 weeks, they have shown that mobile behavioral sensing system could identify both depression and mania states with an accuracy of more than 70% and detect state-change with very high precision and recall [10] . The StudentLife project pioneered the use of mobile behavioral sensing technology for monitoring the daily behavior of college students to assess the impact of academic workload on the students' mental states [11].…”
Section: Related Workmentioning
confidence: 99%
“…Among the pioneer projects, the MONARCA project used a variety of phone sensors such as GPS and accelerometer to detect the mental states as well as changes in mental states of bipolar patients [9]. In their study that involved 12 patients over a period of 12 weeks, they have shown that mobile behavioral sensing system could identify both depression and mania states with an accuracy of more than 70% and detect state-change with very high precision and recall [10] . The StudentLife project pioneered the use of mobile behavioral sensing technology for monitoring the daily behavior of college students to assess the impact of academic workload on the students' mental states [11].…”
Section: Related Workmentioning
confidence: 99%
“…For example, accelerometry and GPS systems that can capture sedentary behaviour or variability in gait have been shown to predict a range of cognitive issues as well as risk of falling [21,22]. Bed restlessness (as measured by a load sensor or a smart watch) can predict a range of health problems in older adults [4,34] and is also seen as one of the most reliable forms of embedded health assessment [47]; and a range of further indicators including speech, mobility and sleep disturbance have been used to predict depression and other forms of mood disorder [11,13,20].…”
Section: Activity Monitoring and The Deficit Modelmentioning
confidence: 99%
“…Additionally, location-based data acquired from mobile devices can be used to assess physical activity [3], exposures to hazardous substances [4], and symptoms of mental health conditions such as depression [5][6][7][8]. Accordingly, there is growing interest in the use of location-tracking devices as a data collection tool for health research.…”
Section: Introductionmentioning
confidence: 99%